KEMAMPUAN MENULIS TULISAN ARAB MELAYU PADA SISWA KELAS VI AL-BAYTAR DI SD IT AL-FITYAH - Hasnah Faizah; Dinda Suliana Rahmanilah; Nurul Syahira; Suci Nur Aini Syah Fitri (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this development research is to produce written Arabic-Malay teaching materials for students majoring in Indonesian Language and Literature Education with content, presentation, language and graphics that are appropriate and effective for learning. This study uses an etographic research model in which ethnographic research is a study of group culture through interviews and observations. The type of research used in this research is quantitative research, which produces numerical data in the form of percentages resulting from the ability to analyze writing in Arabic-Malay script. The research method used is in the form of a test to analyze the ability to write Arabic Malay script